2022
DOI: 10.2478/prolas-2022-0012
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Bioactive and Mineral Compounds in Enteral Tube Feed Products Made of Plant-Based Ingredients

Abstract: Nowadays available products for enteral nutrition are supplemented with synthetic ingredients. The effectiveness of these products is undeniable in the medical industry, but there is concern about bioavailability of synthetic vitamin and mineral compounds in comparison to naturally occurring ones. The aim of this study was to create plant-based formulations for enteral tube feed and to determine their bioactive compound and mineral compound concentration in comparison with the values recommended by the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In addition, similar studies have indicated that sample determination for Se, Zn, K, Mg, and vitamin C differ from (E.U.) 2016/128 requirements for enteral tube feed formulae, raising questions about the bioavailability of synthetic vitamins and minerals in comparison to those from natural sources [8].…”
Section: Understanding Fsmp Composition and Labelling Requirementsmentioning
confidence: 99%
“…In addition, similar studies have indicated that sample determination for Se, Zn, K, Mg, and vitamin C differ from (E.U.) 2016/128 requirements for enteral tube feed formulae, raising questions about the bioavailability of synthetic vitamins and minerals in comparison to those from natural sources [8].…”
Section: Understanding Fsmp Composition and Labelling Requirementsmentioning
confidence: 99%